Blockades of effector T cell senescence and exhaustion synergistically enhance antitumor immunity and immunotherapy. Issue 10 (3rd October 2022) - Liu, Xia; Si, Fusheng; Bagley, David; Ma, Feiya; Zhang, Yuanqin; Tao, Yan; Shaw, Emily; Peng, Guangyong
Abstract : Background: Current immunotherapies still have limited successful rates among cancers. It is now recognized that T cell functional state in the tumor microenvironment (TME) is a key determinant for effective antitumor immunity and immunotherapy. In addition to exhaustion, cellular senescence in tumor-infiltrating T cells (TILs) has recently been identified as an important T cell dysfunctional state induced by various malignant tumors. Therefore, a better understanding of the molecular mechanism responsible for T cell senescence in the TME and development of novel strategies to prevent effector T cell senescence are urgently needed for cancer immunotherapy. Methods: Senescent T cell populations in the TMEs in mouse lung cancer, breast cancer, and melanoma tumor models were evaluated. Furthermore, T cell senescence induced by mouse tumor and regulatory T (Treg) cells in vitro was determined with multiple markers and assays, including real-time PCR, flow cytometry, and histochemistry staining. Loss-of-function strategies with pharmacological inhibitors and the knockout mouse model were used to identify the potential molecules and pathways involved in T cell senescence. In addition, melanoma mouse tumor immunotherapy models were performed to explore the synergistical efficacy of antitumor immunity via prevention of tumor-specific T cell senescence combined with anti-programmed death-ligand 1 (anti-PD-L1) checkpoint blockade therapy. Results: We report that both mouse malignant tumor cells and Treg cells can induce responder T cell senescence, similar as shown in human Treg and tumor cells. Accumulated senescent T cells also exist in the TME in tumor models of lung cancer, breast cancer and melanoma. Induction of ataxia-telangiectasia mutated protein (ATM)-associated DNA damage is the cause for T cell senescence induced by both mouse tumor cells and Treg cells, which is also regulated by mitogen-activated protein kinase (MAPK) signaling. Furthermore, blockages of ATM-associated DNA damage and/or MAPK signaling pathways in T cells can prevent T cell senescence mediated by tumor cells and Treg cells in vitro and enhance antitumor immunity and immunotherapy in vivo in adoptive transfer T cell therapy melanoma models. Importantly, prevention of tumor-specific T cell senescence via ATM and/or MAPK signaling inhibition combined with anti-PD-L1 checkpoint blockade can synergistically enhance antitumor immunity and immunotherapy in vivo. Conclusions: These studies prove the novel concept that targeting both effector T cell senescence and exhaustion is an effective strategy and can synergistically enhance cancer immunotherapy.